A mentor training workshop focused on fostering diversity engenders lasting impact on mentoring techniques: Results of a long-term evaluation. Issue 1 (16th March 2021) - Johnson, Mallory O.; Fuchs, Jonathan D.; Sterling, Lauren; Sauceda, John A.; Saag, Michael S.; Fernandez, Alicia; Evans, Clyde H.; Gandhi, Monica
Abstract: Introduction: Trainees and investigators from underrepresented minority (URM) backgrounds face unique challenges to establishing successful careers in clinical and translational research. Structured training for mentors is an important mechanism to increase the diversity of the research workforce. This article presents data from an evaluation of the University of California, San Francisco (UCSF) Center for AIDS Research (CFAR) Mentoring the Mentors program aimed at improving mentors' competency in working with diverse mentees in HIV research. Methods: Mentors from around the USA who had in one of seven separate 2-day training workshops conducted from 2013 to 2020 were invited to participate in an online evaluation survey of their experiences with the training and their subsequent mentoring activities. Results: There was a high response rate (80%) among the 226 mentors invited to complete the survey. The 180 respondents were diverse in demographics, professional disciplines, and geographic distribution. Quantitative and qualitative data indicate a lasting positive impact of the training, with sustained improvements documented on a validated measure of self-appraised mentoring competency. Respondents also endorsed high interest in future, follow-up training with continued focus on topics related to mentoring in the context of diversity. Conclusion: The evaluation of the UCSF CFAR Mentoring the Mentors program showed lasting impact in improving mentoring practices, coupled with high interest in continued in-depth training in areas focused on diversity, equity, and inclusion.